2023
DOI: 10.1177/00846724231197241
|View full text |Cite
|
Sign up to set email alerts
|

The experience of, and beliefs about, divine grace in mainline protestant Christianity: A consensual qualitative approach

Adam S Hodge,
Jolene Norton,
Logan T Karwoski
et al.

Abstract: The empirical study of grace, a relational virtue, is in its beginning stages. The purpose of this study was to provide rich, context-based, qualitative data to describe Mainline Protestants’ (a) experiences of, and (b) beliefs about, divine grace. Interviews were conducted with 28 community adults who were affiliated with Mainline Protestant Churches. Results indicated that Mainline Protestant Christians have varying beliefs about divine grace and how it is related to both the present moment and the afterlife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, there was also an aspect of guilt or pressure placed on the individual to either (a) seek forgiveness for committing a hurt or offense or (b) respond with forgiveness to an individual who hurt or offended them for a rare number of participants. Although divine grace was defined as a gift by several mainline protestants in this sample (Hodge et al, 2023), the recognition that some participants have these contingencies or rules they follow to experience divine grace suggests that grace may not be perceived as a gift by all Mainline Protestant Christians.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Interestingly, there was also an aspect of guilt or pressure placed on the individual to either (a) seek forgiveness for committing a hurt or offense or (b) respond with forgiveness to an individual who hurt or offended them for a rare number of participants. Although divine grace was defined as a gift by several mainline protestants in this sample (Hodge et al, 2023), the recognition that some participants have these contingencies or rules they follow to experience divine grace suggests that grace may not be perceived as a gift by all Mainline Protestant Christians.…”
Section: Discussionmentioning
confidence: 86%
“…In other words, it appears that grace is difficult to describe outside of other benevolent relational terms (e.g., love, forgiveness). Additionally, Hodge et al (2023) suggested that it may be beneficial to define divine grace as “the totality in which God acts in a benevolent manner towards a receiver, which promotes a sense of connection between the receiver and God,” as only a small number of participants in this study identified grace from God as being a gift or as being unmerited/unearned. However, it may be the case that removing qualifiers such as gift and unmerited may dilute grace to the point where it is impossible to distinguish grace from other related virtues (e.g., charity, kindness).…”
Section: Grace Forgiveness and Humilitymentioning
confidence: 91%
See 3 more Smart Citations